PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP PRAKTIK MANAJEMEN LABA DI BURSA EFEK INDONESIA - Rahadi, Hana Pricila (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The difference of interest between companyâs stakeholders and managers can cause agency problem.This agency problem can lead agency cost to earnings management. The function separation betweenthe companyâs owner and the manager can form a condition which the manager has an opportunity toregulate the profit. The purpose of this research is to examine corporate governance mechanism whichincludes the size of board of directors, the size of board of commissioners, the audit quality, and thetransparency of audit committee to the earnings management. Purposive sampling method is used assample collection method and 35 sample companies have been selected as research object. Thesamples are manufacturing companies which are listed in IDX (Indonesia Stock Exchange) in 2010-2012 periods.The result of analysis that: (1) the size of board of directors has significant positiveinfluence to the earning management, (2) The size of board of commissioners has no influence to theearnings management, (3) audit quality has significant negative influence to the earningsmanagement, (4) the transparency of audit committee has significant negative influence to theearnings management.Keywords:The size of board of directors, the size of board of commissioners, audit quality, the transparency ofaudit committee, and earnings management